Trait versus situation-specific intolerance of uncertainty in a clinical sample with anxiety and depressive disorders - Mahoney, A.; McEvoy, Peter (Routledge, 2012)
Intolerance of uncertainty (IU) has been most heavily implicated in the development and maintenance of generalised anxiety disorder; however, recent research has supported the transdiagnostic conceptualisation of IU by demonstrating that IU contributes to a broad array of symptoms associated with multiple anxiety and depressive disorders. The aim of this study was to examine IU firstly as a trait variable and secondly in reference to a regularly occurring, diagnostically relevant situation in a large clinical sample (N ¼ 218). A measure of situation-specific IU (the Intolerance of Uncertainty Scale–Situation-Specific Version; IUS-SS) is presented. The IUS-SS was found to have a unitary factor structure and high internal consistency. Participants reported significantly more situation-specific IU compared to trait IU. Discriminant validity was indicated by lack of significant relationships with measures of extraversion and alcohol use. Supporting the convergent validity and transdiagnostic nature of the scale, the IUS-SS was positively associated with neuroticism and symptoms of generalised anxiety disorder and social phobia, and explained unique variance in symptoms of depression and panic disorder above and beyond trait IU. Theoretical and clinical implications are discussed.